Identification of Domestic Violence Service Needs Among Child Welfare–Involved Parents With Substance Use Disorders: A Gender-Stratified Analysis - Victor, Bryan G. (Journal of interpersonal violence, 2021)
The current study examined the prevalence and associations of a need for domestic violence services among child welfare–involved mothers and fathers with substance use disorders. Data were drawn from 2,231 child welfare–involved parents in Illinois with an identified substance use disorder. Approximately 42% of mothers and 33% of fathers with a substance use disorder had a concurrent need for domestic violence services. The sample was stratified by gender and logistic regression models were fit to determine the adjusted odds of an identified need for domestic violence services. For both mothers and fathers, the strongest association was an additional need for mental health services. Age, education status, alcohol use, marijuana use, and a reported history of physical violence victimization were also associated with a need for domestic violence services among mothers, while race, age, marital status, annual income, alcohol use, cocaine use, and a reported history of physical violence perpetration were associated with a need for domestic violence services among fathers. The findings of this study make clear that domestic violence is a commonly co-occurring service need for child welfare–involved parents with identified substance use disorders, and that associations with this need vary by gender.